Coated and cutting tools
Patent Information
- Application Number
- JP2023538304
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-07-30
- Filing Date
- 2022-05-27
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-05-27
Smart Images

Figure 0007646009000001 
Figure 0007646009000002 
Figure 0007646009000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to coated tools and cutting tools. [Background technology]
[0002] 2. Description of the Related Art As tools used in cutting processes such as turning and milling, coated tools are known in which the surface of a base material such as cemented carbide, cermet, ceramics, etc. is coated with a coating layer to improve wear resistance and the like. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2020-146777 A [Patent Document 2] Patent No. 5376454 Summary of the Invention
[0004] A coated tool according to an embodiment of the present disclosure includes a substrate and a coating layer located on the substrate. The coating layer includes crystals having a cubic crystal structure. The coating layer has a striped structure in cross-sectional observation by a transmission electron microscope. The striped structure includes two layers that are alternately positioned in the thickness direction. The two layers include Si and at least one type of metal element. The two layers have different contents of metal elements. The two layers each include a crystal having a cubic crystal structure. When a peak angle of a (200) plane of a crystal having a cubic crystal structure obtained by X-ray diffraction of the coating layer is defined as a first angle, and a peak angle of a (200) plane of a crystal having a cubic crystal structure obtained by X-ray diffraction of the coating layer after the coated tool is heat-treated in a nitrogen atmosphere under conditions of a treatment temperature of 900° C. and a treatment time of 1 hour is defined as a second angle, the difference between the first angle and the second angle is 0.05° or less. [Brief description of the drawings]
[0005] [Figure 1] FIG. 1 is a perspective view showing an example of a coated tool according to an embodiment. [Diagram 2] FIG. 2 is a side cross-sectional view showing an example of a coated tool according to an embodiment. [Diagram 3] FIG. 3 is a cross-sectional view showing an example of a coating layer according to the embodiment. [Figure 4] FIG. 4 is a schematic enlarged view of a portion H shown in FIG. [Diagram 5] FIG. 5 is a schematic diagram for illustrating the Al content, the Cr content, and the Si content of the first layer and the second layer. [Figure 6] FIG. 6 is a front view showing an example of a cutting tool according to an embodiment. [Figure 7] FIG. 7 is a table showing the configuration of the coating layer, the measurement results of the first angle and the second angle, and the results of the cutting test for Samples No. 1 to No. 13. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0006] Hereinafter, a detailed description will be given of a form for carrying out a coated tool and a cutting tool according to the present disclosure (hereinafter, referred to as an "embodiment") with reference to the drawings. Note that the coated tool and the cutting tool according to the present disclosure are not limited to the embodiment. Moreover, each embodiment can be appropriately combined as long as the processing contents are not contradictory. Moreover, the same parts in each of the following embodiments are given the same reference numerals, and duplicated explanations will be omitted.
[0007] In addition, in the embodiments described below, expressions such as "constant", "orthogonal", "vertical" and "parallel" may be used, but these expressions do not necessarily mean "constant", "orthogonal", "vertical" and "parallel" strictly. In other words, each of the above expressions allows for deviations due to, for example, manufacturing accuracy and installation accuracy.
[0008] The above-mentioned conventional techniques have room for further improvement in terms of improving thermal stability.
[0009] <Coated tools> Fig. 1 is a perspective view showing an example of a coated tool according to an embodiment. Fig. 2 is a side cross-sectional view showing an example of a coated tool 1 according to an embodiment. As shown in Fig. 1, the coated tool 1 according to the embodiment has a tip body 2.
[0010] (Chip body 2) Chip body 2 has, for example, a hexahedral shape in which the upper and lower surfaces (surfaces intersecting with the Z-axis shown in FIG. 1) are parallelogram-shaped.
[0011] One corner of the tip body 2 functions as a cutting edge portion. The cutting edge portion has a first surface (e.g., an upper surface) and a second surface (e.g., a side surface) connected to the first surface. In the embodiment, the first surface functions as a "scooping surface" that scoops up chips generated by cutting, and the second surface functions as a "flank surface." A cutting edge is located at least in a part of the ridge where the first surface and the second surface intersect, and the coated tool 1 cuts the workpiece by applying the cutting edge to the workpiece.
[0012] A through hole 5 that vertically passes through the tip body 2 is located in the center of the tip body 2. A screw 75 for attaching the coated tool 1 to a holder 70 (described later) is inserted into the through hole 5 (see FIG. 6).
[0013] As shown in FIG. 2, the chip body 2 has a base 10 and a covering layer 20.
[0014] (Base 10) The substrate 10 is formed of, for example, a cemented carbide. The cemented carbide contains W (tungsten), specifically WC (tungsten carbide). The cemented carbide may also contain Ni (nickel) and / or Co (cobalt). Specifically, the substrate 10 is made of a WC-based cemented carbide containing WC particles as a hard phase component and Co as a main component of a binder phase.
[0015] The substrate 10 may be made of a cermet. The cermet contains, for example, Ti (titanium), specifically, TiC (titanium carbide) or TiN (titanium nitride). The cermet may also contain Ni or Co.
[0016] The substrate 10 may be formed of a cubic boron nitride sintered body containing cubic boron nitride (cBN) particles. The substrate 10 is not limited to cubic boron nitride (cBN) particles, and may contain particles of hexagonal boron nitride (hBN), rhombohedral boron nitride (rBN), wurtzite boron nitride (wBN), or the like.
[0017] (Coating layer 20) The coating layer 20 is applied to the substrate 10 for the purpose of improving the wear resistance, heat resistance, etc. of the substrate 10. In the example of FIG. 2, the coating layer 20 covers the entire substrate 10. The coating layer 20 needs to be located at least on the substrate 10. When the coating layer 20 is located on the first surface (here, the upper surface) of the substrate 10, the wear resistance and heat resistance of the first surface are high. When the coating layer 20 is located on the second surface (here, the side surface) of the substrate 10, the wear resistance and heat resistance of the second surface are high.
[0018] Here, a specific configuration of the coating layer 20 will be described with reference to Fig. 3 and Fig. 4. Fig. 3 is a cross-sectional view showing an example of the coating layer 20 according to the embodiment. Fig. 4 is a schematic enlarged view of a portion H shown in Fig. 3.
[0019] As shown in FIG. 3, the coating layer 20 has a first coating layer 23 located on the intermediate layer 22 and a second coating layer 24 located on the first coating layer 23.
[0020] (1st coating layer 23) The first coating layer 23 contains at least one element selected from the group consisting of Al, Group 5 elements, Group 6 elements, and Group 4 elements excluding Ti, at least one element selected from the group consisting of C and N, Si, and Cr.
[0021] Specifically, the first coating layer 23 may contain Al, Cr, Si, and N. That is, the first coating layer 23 may be an AlCrSiN layer containing AlCrSiN, which is a nitride of Al, Cr, and Si. Note that the expression "AlCrSiN" means that Al, Cr, Si, and N are present in any ratio, and does not necessarily mean that Al, Cr, Si, and N are present in a 1:1:1:1:1 ratio.
[0022] When the first coating layer 23 containing the metal (e.g., Si) contained in the intermediate layer 22 is positioned on the intermediate layer 22, the adhesion between the intermediate layer 22 and the coating layer 20 is high. As a result, the coating layer 20 is less likely to peel off from the intermediate layer 22, and the durability of the coating layer 20 is high.
[0023] As shown in Fig. 4, the first coating layer 23 may have a striped structure when observed in cross section by a transmission electron microscope. Specifically, the first coating layer 23 has a plurality of first layers 23a and a plurality of second layers 23b. In the first coating layer 23, the first layers 23a and the second layers 23b are alternately laminated in the thickness direction. The first layers 23a are layers in contact with the intermediate layer 22, and the second layers 23b are formed on the first layers 23a.
[0024] The thickness of each of the first layer 23a and the second layer 23b may be 50 nm or less. The first layer 23a and the second layer 23b formed thinly have small residual stress and are less likely to peel off or crack, so that the durability of the coating layer 20 is increased.
[0025] The first coating layer 23 may contain crystals having a cubic crystal structure. In this case, the first layer 23a and the second layer 23b may each contain crystals having a cubic crystal structure.
[0026] The first layer 23a and the second layer 23b may contain Si and at least one type of metal element, and the content of the metal element may be different between the first layer 23a and the second layer 23b.
[0027] FIG. 5 is a schematic diagram for illustrating the Al content, the Cr content, and the Si content of the first layer 23a and the second layer 23b.
[0028] The first layer 23a and the second layer 23b contain Al, Cr, Si, and N. Here, the Al content in the first layer 23a is referred to as the first Al content, the Cr content in the first layer 23a is referred to as the first Cr content, and the Si content in the first layer 23a is referred to as the first Si content. The Al content in the second layer 23b is referred to as the second Al content, the Cr content in the second layer 23b is referred to as the second Cr content, and the Si content in the second layer 23b is referred to as the second Si content.
[0029] In this case, the first Al content may be greater than the second Al content, the first Cr content may be less than the second Cr content, and the first Si content may be greater than the second Si content.
[0030] The coated tool 1 having the first coating layer 23 having such a configuration has high hardness and excellent chipping resistance.
[0031] Furthermore, the total content of Al, Cr, and Si in the metal elements contained in the first coating layer 23 may be 98 atomic % or more.
[0032] The coated tool 1 having the first coating layer 23 having such a configuration has even higher hardness and excellent chipping resistance.
[0033] The ratio of Al to the metal elements in the first coating layer 23 may be 38 atomic % or more and 55 atomic % or less. The ratio of Cr to the metal elements in the first coating layer 23 may be 33 atomic % or more and 48 atomic % or less. The ratio of Si to the metal elements in the first coating layer 23 may be 4 atomic % or more and 15 atomic % or less.
[0034] The coated tool 1 having the first coating layer 23 having such a configuration has improved oxidation resistance and excellent wear resistance.
[0035] The difference between the first Al content and the second Al content may be 1 atomic % or more and 9 atomic % or less.
[0036] The coated tool 1 having the first coating layer 23 having such a configuration maintains high oxidation resistance and high hardness, while relieving stress inside the coating layer and providing excellent wear resistance.
[0037] The coated tool 1 having the first coating layer 23 having such a configuration has particularly high hardness.
[0038] The difference between the first Cr content and the second Cr content may be 1 atomic % or more and 12 atomic % or less.
[0039] The coated tool 1 having the first coating layer 23 having such a configuration has even more excellent wear resistance.
[0040] The coated tool 1 having the first coating layer 23 having such a configuration is particularly excellent in fracture resistance.
[0041] The difference between the first Si content and the second Si content may be 0.5 atomic % or more and 5 atomic % or less.
[0042] The coated tool 1 having the first coating layer 23 having such a configuration has particularly high hardness.
[0043] The thickness of the first layer 23a and the second layer 23b may be not less than 1 nm and not more than 20 nm.
[0044] The coated tool 1 having the first coating layer 23 having such a configuration is excellent in hardness and chipping resistance.
[0045] The first coating layer may be formed by, for example, a physical vapor deposition method. Examples of physical vapor deposition methods include an ion plating method and a sputtering method. As an example, when the first coating layer is formed by an ion plating method, the coating layer can be formed by the following method.
[0046] First, for example, metal targets of Cr, Si and Al, or composite alloy targets, or sintered compact targets are prepared.
[0047] Next, the above target, which is the metal source, is evaporated and ionized by arc discharge or glow discharge. The ionized metal is reacted with nitrogen (N2) gas, which is the nitrogen source, and is evaporated onto the surface of the substrate. The above procedure makes it possible to form an AlCrSiN layer.
[0048] In the above procedure, the temperature of the substrate may be 500 to 600° C., the pressure may be 1.0 to 6.0 Pa, a DC bias voltage of −50 to −200 V may be applied to the substrate, and the arc discharge current may be 100 to 200 A.
[0049] The composition of the first coating layer can be adjusted by independently controlling the voltage and current values during arc discharge and glow discharge applied to the aluminum metal target, the chromium metal target, the aluminum-silicon composite alloy target, and the chromium-silicon composite alloy target for each target. The composition of the first coating layer can also be adjusted by controlling the coating time and the atmospheric gas pressure. In one embodiment, the amount of ionization of the target metal can be changed by changing the voltage and current values during arc discharge and glow discharge. The amount of ionization of the target metal can be changed periodically by periodically changing the current value during arc discharge and glow discharge for each target. The amount of ionization of the target metal can be changed periodically by periodically changing the current value during arc discharge and glow discharge of the target at intervals of 0.01 to 0.5 min. This allows the coating layer to have a configuration in which the content ratio of each metal element changes in each period in the thickness direction.
[0050] When carrying out the above procedure, it is possible to produce a first coating layer 23 having a first layer and a second layer by changing the composition of Al, Si, and Cr so that the amounts of Al and Si are smaller and the amount of Cr is larger, and then changing the composition of Al, Si, and Cr so that the amounts of Al and Si are larger and the amount of Cr is smaller.
[0051] (Second coating layer 24) The second coating layer 24 may contain Ti, Si, and N. That is, the second coating layer 24 may be a nitride layer (TiSiN layer) containing Ti and Si. Note that the expression "TiSiN layer" means that Ti, Si, and N are present in any ratio, and does not necessarily mean that Ti, Si, and N are present in a 1:1:1 ratio.
[0052] As a result, for example, when the friction coefficient of the second coating layer 24 is low, the adhesion resistance of the coated tool 1 can be improved. Also, for example, when the hardness of the second coating layer 24 is high, the wear resistance of the coated tool 1 can be improved. Also, for example, when the oxidation onset temperature of the second coating layer 24 is high, the oxidation resistance of the coated tool 1 can be improved.
[0053] The second coating layer 24 may have a striped structure in cross-sectional observation by a transmission electron microscope. Specifically, the second coating layer 24 may have two or more layers located in the thickness direction. For example, the second coating layer 24 may have a third layer and a fourth layer alternately located in the thickness direction. The second coating layer 24 may also contain crystals having a cubic crystal structure. In this case, each layer constituting the striped structure of the second coating layer 24 may contain crystals having a cubic crystal structure.
[0054] Each layer in the striped structure of the second coating layer 24 may contain Si and at least one type of metal element, and the content of the metal element may differ from layer to layer.
[0055] In the second coating layer 24, the Ti content (hereinafter referred to as the "Ti content"), the Si content (hereinafter referred to as the "Si content"), and the N content (hereinafter referred to as the "N content") may each repeatedly increase and decrease along the thickness direction of the second coating layer 24. Among the metal elements contained in the second coating layer 24, the total of Ti and Si may be 98 atomic % or more.
[0056] The coated tool 1 having the second coating layer 24 with such a configuration has improved toughness of the coating layer and is excellent in impact resistance. Specifically, the coated tool 1 having the second coating layer 24 with such a configuration is excellent in fracture resistance and chipping resistance.
[0057] The second coating layer 24 may have a portion where the cycle of increase and decrease of the Ti content is different from the cycle of increase and decrease of the Si content. Here, the cycle of increase and decrease means, for example, the distance from the position where the Ti content (Si content) is maximum (or minimum) to the position where it is next maximum (or minimum) along the thickness direction of the second coating layer 24.
[0058] The coated tool 1 having the second coating layer 24 having such a configuration maintains high hardness while improving toughness and providing excellent impact resistance.
[0059] The period of increase / decrease in the Ti content, the period of increase / decrease in the Si content, and the period of increase / decrease in the N content may be 1 nm or more and 15 nm or less.
[0060] In the coated tool 1 having the second coating layer 24 having such a configuration, the residual stress inside the coating layer is relaxed, the adhesion of the coating layer is improved, and the impact resistance is improved.
[0061] The ratio of Ti to the metal elements in the second coating layer 24 may be 80 atomic % or more and 95 atomic % or less, and the ratio of Si to the metal elements in the second coating layer 24 may be 5 atomic % or more and 20 atomic % or less.
[0062] The coated tool 1 having the second coating layer 24 of such a configuration has improved adhesion of the coating layer while maintaining high hardness, and further has excellent toughness of the coating layer, thereby exhibiting high impact resistance.
[0063] The ratio of Ti to the metal elements in the second coating layer 24 may be 82 atomic % or more and 90 atomic % or less.
[0064] The coated tool 1 having the second coating layer 24 having such a configuration has further improved toughness and exhibits high impact resistance.
[0065] The second coating layer 24 may be formed by physical vapor deposition, like the first coating layer 23. As an example, the second coating layer made of TiSiN having a striped structure can be produced by using a titanium metal target and a titanium-silicon composite alloy target in an ion plating method, and independently controlling the voltage and current values during arc discharge and glow discharge applied to these targets for each target.
[0066] The first angle is the peak angle of the (200) plane of crystals having a cubic crystal structure obtained by X-ray diffraction of the coating layer 20 having the first coating layer 23 and the second coating layer 24. The second angle is the peak angle of the (200) plane of crystals having a cubic crystal structure obtained by X-ray diffraction of the coating layer 20 after the coated tool 1 on which the coating layer 20 having the first coating layer 23 and the second coating layer 24 is formed is heat-treated in a nitrogen atmosphere at a treatment temperature of 900°C for a treatment time of 1 hour. In this case, the difference between the first angle and the second angle may be 0.05° or less.
[0067] Conventionally, a coating layer in which two layers are alternately stacked has a large peak shift (amount of change in peak angle) of the (200) plane before and after heat treatment. For this reason, a coated tool having a conventional laminated film has low thermal stability and low wear resistance and thermal shock resistance during cutting. In contrast, the coating layer 20 according to the embodiment has a difference between the first angle and the second angle of 0.05° or less, that is, the peak shift of the (200) plane before and after heat treatment is small. For this reason, the coated tool 1 according to the embodiment has high thermal stability and can improve performance degradation such as wear resistance and thermal shock resistance during cutting.
[0068] Moreover, in the coating layer 20, both the first coating layer 23 and the second coating layer 24 contain Si. This can reduce the residual stress generated between the layers, thereby further improving the thermal stability.
[0069] Moreover, the coating layer 20 has a first coating layer 23 containing Al and Cr, which can improve the oxidation resistance and lubricity of the coating layer 20.
[0070] Moreover, the coating layer 20 has a second coating layer 24 containing Ti, which can improve chipping resistance.
[0071] Here, an example in which the coating layer 20 has both the first coating layer 23 and the second coating layer 24 has been described, but the coating layer 20 may have at least one of the first coating layer 23 and the second coating layer 24. That is, the coating layer 20 may have only the first coating layer 23 of the first coating layer 23 and the second coating layer 24. The coating layer 20 may have only the second coating layer 24 of the first coating layer 23 and the second coating layer 24. Even in these cases, the thermal stability can be improved by setting the difference between the first angle and the second angle to 0.05° or less.
[0072] (Middle layer 22) An intermediate layer 22 may be located between the substrate 10 and the coating layer 20. Specifically, the intermediate layer 22 contacts the upper surface of the substrate 10 on one side (here, the lower surface) and contacts the lower surface of the coating layer 20 (first coating layer 23) on the other side (here, the upper surface).
[0073] The intermediate layer 22 has higher adhesion to the substrate 10 than the coating layer 20. Examples of metal elements having such properties include Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si, Y, and Ti. The intermediate layer 22 contains at least one of the above metal elements. For example, the intermediate layer 22 may contain Ti. Note that Si is a metalloid element, but in this specification, metalloid elements are also included in the metal elements.
[0074] When the intermediate layer 22 contains Ti, the Ti content in the intermediate layer 22 may be 1.5 atomic % or more. For example, the Ti content in the intermediate layer 22 may be 2.0 atomic % or more.
[0075] Intermediate layer 22 may contain components other than the above metal elements (Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si, Y, Ti). However, from the viewpoint of adhesion to substrate 10, intermediate layer 22 may contain the above metal elements in a total amount of at least 95 atomic % or more. More preferably, intermediate layer 22 may contain the above metal elements in a total amount of 98 atomic % or more. The proportion of the metal components in intermediate layer 22 can be identified by, for example, analysis using an EDS (energy dispersive X-ray spectrometer) attached to a STEM (scanning transmission electron microscope).
[0076] In this way, in the coated tool 1 according to the embodiment, the intermediate layer 22, which has higher wettability with the substrate 10 than the coating layer 20, is provided between the substrate 10 and the coating layer 20, thereby improving the adhesion between the substrate 10 and the coating layer 20. Since the intermediate layer 22 also has high adhesion with the coating layer 20, peeling of the coating layer 20 from the intermediate layer 22 is unlikely to occur.
[0077] The thickness of the intermediate layer 22 may be, for example, not less than 0.1 nm and less than 20.0 nm.
[0078] <Cutting tools> Next, the configuration of a cutting tool including the above-mentioned coated tool 1 will be described with reference to Fig. 6. Fig. 6 is a front view showing an example of a cutting tool according to an embodiment.
[0079] As shown in FIG. 6, a cutting tool 100 according to the embodiment includes a coated tool 1 and a holder 70 for fixing the coated tool 1.
[0080] The holder 70 is a rod-shaped member extending from a first end (the upper end in FIG. 6) to a second end (the lower end in FIG. 6). The holder 70 is made of, for example, steel or cast iron. Of these materials, it is particularly preferable to use steel, which has high toughness.
[0081] The holder 70 has a pocket 73 at the end on the first end side. The pocket 73 is a portion where the coated tool 1 is attached, and has a seating surface that intersects with the rotation direction of the workpiece and a constraint side surface that is inclined relative to the seating surface. The seating surface is provided with a screw hole into which a screw 75, which will be described later, is screwed.
[0082] The coated tool 1 is positioned in a pocket 73 of the holder 70, and is attached to the holder 70 by a screw 75. That is, the screw 75 is inserted into the through hole 5 of the coated tool 1, and the tip of the screw 75 is inserted into a screw hole formed in the seating surface of the pocket 73 to screw the threaded portions together. In this way, the coated tool 1 is attached to the holder 70 such that the cutting edge portion protrudes outward from the holder 70.
[0083] In the embodiment, a cutting tool used in so-called turning is exemplified. Examples of turning include inner diameter machining, outer diameter machining, and grooving. The cutting tool is not limited to that used in turning. For example, the coated tool 1 may be used as a cutting tool used in turning. Examples of cutting tools used in turning include milling cutters such as flat milling cutters, face milling cutters, side milling cutters, and groove milling cutters, and end mills such as single-blade end mills, multiple-blade end mills, tapered-blade end mills, and ball end mills. EXAMPLES
[0084] Examples of the present disclosure will be specifically described below. Note that the present disclosure is not limited to the examples shown below.
[0085] Samples No. 1 to No. 13 were prepared, each having a coating layer on a substrate made of a WC-based cemented carbide containing WC particles as the hard phase component and Co as the main component of the binder phase. Of Samples No. 1 to No. 13, the coating layers of Samples No. 1 to No. 9 all have a striped structure when observed in cross section by a transmission electron microscope. The coating layers of Samples No. 10 to No. 13 all do not have a striped structure when observed in cross section by a transmission electron microscope. Samples No. 1 to No. 3 correspond to examples of the present disclosure, and Samples No. 4 to No. 13 correspond to comparative examples.
[0086] A coated tool in which the substrate is made of WC, the intermediate layer is made of a Ti-containing layer, the first coating layer is made of an AlCrSiN layer, and the second coating layer is made of a TiSiN layer was used as Sample No. 1. Sample No. 1 corresponds to an example of the present disclosure.
[0087] 1×10 -3 The substrate was heated in a reduced-pressure environment of 1×10 Pa to a surface temperature of 550°C. Next, argon gas was introduced as the atmospheric gas, and the pressure was maintained at 3.0 Pa. Next, with the bias voltage set to -400 V, argon bombardment treatment was performed for 11 minutes. Next, the pressure was reduced to 0.1 Pa, an arc current of 150 A was applied to the Ti metal evaporation source, and the treatment was performed for 0.3 minutes to form a Ti-containing layer as an intermediate layer on the surface of the substrate. The argon bombardment treatment and the Ti-containing intermediate layer formation treatment were repeated a total of 3 times to form a Ti-containing intermediate layer with a layer thickness of 8 nm. However, in the second and third argon bombardment treatments, the bias voltage was set to -200 V.
[0088] <Processing conditions for argon bombardment treatment> (1) Bias voltage: -400 V (2) Pressure: 3 Pa (3) Processing time: 11 minutes
[0089] <Film formation conditions for Ti-containing layer> (1) Arc current: 150 A (2) Bias voltage: -400 V (3) Pressure: 0.1 a (4) Processing time: 0.3 minutes
[0090] <Processing conditions for argon bombardment treatment after the second time> (1) Bias voltage: -200 V (2) Pressure: 3 Pa (3) Processing time: 1 minute
[0091] The Ti-containing layer may contain other metal elements by diffusion, for example. The Ti-containing layer may contain 50 to 98 atomic% of metal elements other than Ti.
[0092] Next, the first coating layer was formed. N2 gas was introduced into the chamber containing the substrate as an atmospheric gas and a N source, and the pressure inside the chamber was maintained at 3 Pa. Next, Al metal, Cr metal, and Al 52 S 48 A bias voltage of -130 V and an arc current of 135 to 150 A, 120 to 150 A, and 110 to 120 A were applied to the alloy evaporation source for 15 min, and each arc current was repeatedly applied at a cycle of 0.04 min to form a first coating layer (Al 50 Cr 43 Si7)N / (Al 48 Cr 45 A Si7)N layer was formed.
[0093] Next, a second coating layer was formed. 52 S 48 A bias voltage of -100 V and an arc current of 100 to 200 A and 100 to 200 A were applied to the alloy evaporation source for 10 min, repeatedly at a cycle of 0.04 min. The second coating layer (Ti 91 Si9)N / (Ti 89 S 11 )N layer was formed.
[0094] Samples No. 2 to No. 13 were prepared according to the method for preparing sample No. 1, but by changing the metal or alloy evaporation source.
[0095] The coating layers of Samples No. 1 to No. 9 have a striped structure. Of Samples No. 1 to No. 9, the coating layers of Samples No. 1 to No. 3 and No. 6 contain Si in each of two layers that are alternately positioned in the thickness direction.
[0096] The coating layers of Samples No. 4, No. 5, and No. 9 do not contain Si in any of the two layers positioned alternately in the thickness direction.
[0097] The coating layers of samples No. 7 and No. 8 are arranged alternately in the thickness direction, one of which contains Si and the other does not contain Si.
[0098] Among samples No. 1 to No. 13, the coating layers of samples No. 10 to No. 13 do not have a striped structure. The coating layers of samples No. 10 to No. 13 do not contain Si.
[0099] The first angle and the second angle were measured for each of Samples No. 1 to No. 13. As described above, the first angle is the peak angle of the (200) plane of the crystal having a cubic crystal structure contained in the coating layer. The second angle is the peak angle of the (200) plane of the crystal having a cubic crystal structure after each of Samples No. 1 to No. 13 was heat-treated in a nitrogen atmosphere at a treatment temperature of 900°C for a treatment time of 1 hour.
[0100] The first and second angles were measured using a thin-film X-ray diffraction device "X'Pert PRO-MRD (DY2295)" (PANalytical). The optical system of this device is an X-ray mirror and a flat collimator. The X-ray tube of this device is CuKα, and the output is 45kV / 40mA.
[0101] The measurement conditions are as follows. Measurement method: 2θ scan Measurement range: 20°~80° Incident angle: 0.5° Step: 0.02° Time:4.0sec / step
[0102] The peak of the (200) plane of a crystal having a cubic crystal structure is a peak seen at an angle of 42° to 44° under the above conditions.
[0103] In addition, samples No. 1 to No. 13 were subjected to the following conditions using a two-blade carbide ball end mill (model number: 2KMBL0200-0800-S4).
[0104] <Cutting test conditions> (1) Cutting method: Pocket machining (2) Work material: SKD11H (3) Rotational speed: 16,900 min -1 (4) Table feed: 1320 mm / min (5) Depth of cut (ap x ae): 0.08 mm x 0.2 mm (6) Cutting condition: Wet (7) Coolant: Oil mist (8) Evaluation method: Evaluation was based on the number of impacts until chipping occurred.
[0105] FIG. 7 is a table showing the configuration of the coating layer, the measurement results of the first angle and the second angle, and the results of the cutting test for Samples No. 1 to No. 13.
[0106] The coating layer of sample No. 1 has a first coating layer and a second coating layer. The first coating layer has a first layer and a second layer that are alternately positioned in the thickness direction. The second coating layer has a third layer and a fourth layer that are alternately positioned in the thickness direction. The first layer and the second layer have Al, Cr, Si, and N. The ratios of Al, Cr, and Si in the metal elements of the first layer are 50 atomic %, 43 atomic %, and 7 atomic %, respectively, and the ratios of Al, Cr, and Si in the metal elements of the second layer are 48 atomic %, 46 atomic %, and 6 atomic %, respectively. The third layer and the fourth layer have Ti and Si. The ratios of Ti and Si in the metal elements of the third layer are 91 atomic % and 9 atomic %, respectively, and the ratios of Ti and Si in the metal elements of the fourth layer are 89 atomic % and 11 atomic %, respectively.
[0107] The coating layer of sample No. 2 has only the first coating layer out of the first coating layer and the second coating layer. The first coating layer has a first layer and a second layer alternately positioned in the thickness direction, and the first layer and the second layer have Al, Cr, Si, and N. The ratios of Al, Cr, and Si in the metal elements of the first layer are 50 atomic %, 43 atomic %, and 7 atomic %, respectively, and the ratios of Al, Cr, and Si in the metal elements of the second layer are 48 atomic %, 46 atomic %, and 6 atomic %, respectively.
[0108] The coating layer of sample No. 3 has the second coating layer of the first and second coating layers. The second coating layer has a third layer and a fourth layer alternately positioned in the thickness direction, and the third layer and the fourth layer have Ti, Si, and N. The ratios of Ti and Si in the metal elements of the third layer are 91 atomic % and 9 atomic %, respectively, and the ratios of Ti and Si in the metal elements of the fourth layer are 89 atomic % and 11 atomic %, respectively.
[0109] The coating layer of sample No. 4 has two layers (referred to as "fifth layer" and "sixth layer") that are alternately positioned in the thickness direction. The fifth layer contains Al, Cr, and N, and the sixth layer contains Al, Ti, and N. The ratios of Al and Cr in the metal elements of the fifth layer are 50 atomic % and 50 atomic %, respectively, and the ratios of Al and Ti in the metal elements of the sixth layer are 60 atomic % and 40 atomic %, respectively.
[0110] The coating layer of sample No. 5 has two layers (referred to as "seventh layer" and "eighth layer") that are alternately positioned in the thickness direction. The seventh layer contains Ti, Al, and N, and the eighth layer contains Al, Cr, and N. The ratios of Ti and Al among the metal elements in the seventh layer are 70 atomic % and 30 atomic %, respectively, and the ratios of Al and Cr among the metal elements in the eighth layer are 50 atomic % and 50 atomic %, respectively.
[0111] The coating layer of sample No. 6, like the coating layer of sample No. 1, has a first coating layer of (AlCrSi)N / (AlCrSi) and a second coating layer of (TiSi)N / (TiSi)N. The first and second coating layers of the coating layer of sample No. 6 have different composition ratios from the first and second coating layers of the coating layer of sample No. 1. Specifically, sample No. 6 has a first coating layer of (Al 59 Cr 22 Si9)N / (Al 77 Cr 11 S 12 )N layer, and the second coating layer is (Ti 78 S 22 )N / (Ti 75 S 25)N layers.
[0112] That is, the first coating layer of sample No. 6 has a 9th layer and a 10th layer alternately positioned in the thickness direction. The 9th layer and the 10th layer contain Al, Cr, Si, and N. The ratios of Al, Cr, and Si in the metal elements of the 9th layer are 59 atomic %, 22 atomic %, and 9 atomic %, respectively, and the ratios of Al, Cr, and Si in the metal elements of the 10th layer are 77 atomic %, 11 atomic %, and 12 atomic %, respectively. The second coating layer of sample No. 6 has an 11th layer and a 12th layer alternately positioned in the thickness direction. The 11th layer and the 12th layer contain Ti and Si. The ratios of Ti and Si in the metal elements of the 11th layer are 78 atomic % and 22 atomic %, respectively, and the ratios of Ti and Si in the metal elements of the 12th layer are 75 atomic % and 25 atomic %, respectively.
[0113] The coating layer of sample No. 7 has two layers, a 13th layer and a 14th layer, which are alternately positioned in the thickness direction. The 13th layer contains Al, Cr, Si, and N, and the 14th layer contains Al, Cr, and N. The ratios of Al, Cr, and Si in the metal elements of the 13th layer are 50 atomic %, 43 atomic %, and 7 atomic %, respectively, and the ratios of Al and Cr in the metal elements of the 14th layer are 51 atomic % and 49 atomic %, respectively.
[0114] The coating layer of sample No. 8 has two layers, a 15th layer and a 16th layer, which are alternately positioned in the thickness direction. The 15th layer contains Al, Cr, Si, and N, and the 16th layer contains Al, Cr, and N. The ratios of Al, Cr, and Si in the metal elements of the 15th layer are 53 atomic %, 45 atomic %, and 2 atomic %, respectively, and the ratios of Al and Cr in the metal elements of the 16th layer are 51 atomic % and 49 atomic %, respectively.
[0115] The coating layer of sample No. 9 has two layers, a 17th layer and a 18th layer, which are alternately positioned in the thickness direction. The 17th layer contains Ti and N, and the 18th layer contains Ti, Cr and N. The ratios of Ti and Cr in the metal elements of the 18th layer are 50 atomic % and 50 atomic %, respectively.
[0116] The coating layer of sample No. 10 contains Ti and N. The coating layer of sample No. 11 contains Ti, Cr and N. The ratios of Ti and Cr are 50 atomic % and 50 atomic %, respectively. The coating layer of sample No. 12 contains Cr and N. The coating layer of sample No. 13 contains Al, Ti and N. The ratios of Al and Ti are 60 atomic % and 40 atomic %, respectively.
[0117] As shown in Fig. 7, the difference between the first angle and the second angle was 0.02° for sample No. 1, 0.04° for sample No. 2, 0.03° for sample No. 3, 1.17° for sample No. 4, 0.12° for sample No. 5, and 0.08° for sample No. 6. In addition, the difference between the first angle and the second angle was 0.05° for sample No. 7, 0.07° for sample No. 8, 0.05° for sample No. 9, 0.04° for sample No. 10, 0.05° for sample No. 11, 0.04° for sample No. 12, and 1.21° for sample No. 13.
[0118] Thus, samples No. 1 to No. 3, which correspond to examples of the present disclosure, have a smaller difference between the first angle and the second angle than samples No. 1 to No. 9, which have a striped structure among samples No. 4 to No. 13, which correspond to comparative examples. This result shows that the coated tool according to the present disclosure has higher thermal stability than samples No. 4 to No. 9. Note that sample No. 1 has a first coating layer and a second coating layer, but the result shown in FIG. 7 is the difference between the first angle and the second angle in the second coating layer.
[0119] As shown in Figure 7, the number of impacts until chipping in the cutting test was 127,000 for sample No. 1, 122,000 for sample No. 2, 123,000 for sample No. 3, 33,000 for sample No. 4, and 30,000 for sample No. 5. The number of impacts was 95,000 for sample No. 6, 85,000 for sample No. 7, 72,000 for sample No. 8, and 22,000 for sample No. 9. The number of impacts was 14,000 for sample No. 10, 17,000 for sample No. 11, 15,000 for sample No. 12, and 26,000 for sample No. 13.
[0120] Thus, Samples No. 1 to No. 3, which correspond to examples of the present disclosure, required a greater number of impacts before chipping occurred, compared to the comparative samples No. 4 to No. 13. These results show that the coated tools according to the present disclosure have higher wear resistance and thermal shock resistance during cutting, compared to the comparative samples No. 4 to No. 13.
[0121] As described above, the coated tool according to the embodiment (the coated tool 1 as an example) is a coated tool having a base (the base 10 as an example) and a coating layer (the coating layer 20 as an example) located on the base. The coating layer contains crystals having a cubic crystal structure. The coating layer has a striped structure in cross-sectional observation by a transmission electron microscope. The striped structure has two layers that are alternately located in the thickness direction. The two layers contain Si and at least one type of metal element. The two layers have different contents of metal elements. The two layers each contain crystals having a cubic crystal structure. When the peak angle of the (200) plane of the crystals having a cubic crystal structure in the coating layer obtained by X-ray diffraction is taken as a first angle, and the peak angle of the (200) plane of the crystals having a cubic crystal structure in the coating layer obtained by X-ray diffraction after the coated tool is heat-treated in a nitrogen atmosphere under conditions of a treatment temperature of 900°C and a treatment time of 1 hour is taken as a second angle, the difference between the first angle and the second angle is 0.05° or less.
[0122] Therefore, according to the coated tool according to the embodiment, it is possible to improve the thermal stability.
[0123] 1 is merely an example and does not limit the shape of the coated tool according to the present disclosure. The coated tool according to the present disclosure may have, for example, a rod-shaped main body having a rotation axis and extending from a first end to a second end, a cutting edge located at the first end of the main body, and a groove extending spirally from the cutting edge toward the second end of the main body.
[0124] Further advantages and modifications may readily occur to those skilled in the art. Thus, the invention in its broader aspects is not limited to the specific details and representative embodiments shown and described above. Accordingly, various modifications may be made without departing from the spirit or scope of the general inventive concept as defined by the appended claims and equivalents thereof. [Explanation of symbols]
[0125] 1. Coated tools 2 Chip body 5 Through hole 10 Base 20 Covering layer 22 Middle Class 23 First coating layer 24 Second coating layer 70 Holder 73 Pocket 75 Screw 100 cutting tools
Claims
1. A coated tool having a substrate and a coating layer overlying the substrate, The coating layer contains crystals having a cubic crystal structure, The coating layer has a striped structure when observed in cross section by a transmission electron microscope, The striped structure has two layers that are alternately positioned in the thickness direction, The two layers include a nitride having Si and at least one metal element; The at least one metal element is Al and Cr or Ti, The contents of the metal elements are different from each other, Each of the crystals has a cubic crystal structure, a peak angle of a (200) plane of the crystal having a cubic structure in the coating layer by X-ray diffraction is defined as a first angle; The coated tool is heat-treated in a nitrogen atmosphere at a treatment temperature of 900° C. for a treatment time of 1 hour, and then a peak angle of a (200) plane of the crystal having a cubic crystal structure obtained by X-ray diffraction of the coating layer is defined as a second angle. A coated tool, wherein the difference between the first angle and the second angle is 0.05° or less.
2. the coating layer includes a first coating layer located on the substrate and a second coating layer located on the first coating layer; the first coating layer and the second coating layer each have a striped structure when cross-sectionally observed with a transmission electron microscope; The striped structure of the first coating layer includes first layers and second layers that are alternately positioned in a thickness direction, The striped structure of the second coating layer includes a third layer and a fourth layer that are alternately positioned in a thickness direction, the first layer and the second layer include Al, Cr, Si, and N; The coated tool of claim 1 , wherein the third layer and the fourth layer comprise Ti, Si, and N.
3. a rod-shaped holder having a pocket at one end; The coated tool according to claim 1 or 2, located in the pocket; A cutting tool having
Citation Information
Patent Citations
Frosttdetecting device
JP1978076454A
Drawing reader
JP1985004366A
Hard film coated member, and its coating method
JP2006137982A
Coated member with hard film and coating method therefor
JP2006152321A
Surface-coated cutting tool having hard coating layer exerting excellent abrasion resistance in high-speed cutting of high-hardness steel
JP2007069276A